RESOLUTION OF DISPUTES OF OUTSOURCING WORK FORCE IN THE COMPANY EMPLOYING OUTSOURCING SERVICE - Pupu Sriwulan Sumaya (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
Generally, the development of the stage of world’s implementation of outsourcing in globalization era increases significantly. In the field of work force, outsourcing is constitutes as the use of work force to produce or execute the work by a company, through a work force supplying company. In the implementation of outsourcing, the potential of disputes may arise, in some sort of violation of company rules by some workers or the emerging disputes between the outsourcing worker with another worker, disputes over the wage, social security of the worker, different requirements of the worker. Issues of interests between Outsourcing and the supplying company sometimes bring many problems in industrial relationship, complex of industrial relationships frequently bring disputes between outsourcing as labors and the supplying company. It can be said that the disputes of industrial relationship will always occur among labors and the employer. Therefore, outsourcing mostly is intentionally implemented to press the labor cost with law protected and the working requirements which are given under the standard given so that it harms the worker/labor. Referring to article 66 verse (2) letter c of the Act No 13 Year 2003 on Labor, the resolution of disputes that emerge becomes the responsibility of the company supplying the labors. The dispute of the parties mostly occur when one the parties has other party to do or not to do something, yet the other party refuse to obey it. So it happens in industrial relationship, only the scale of the scope is around the interest of the worker/labor, employer, and the government, therefore these three subject of law is the pillar to support the success of the implementation of law of labor including for the success of the resolution of disputes on industrial relationship. Keywords: Outsourcing worker, Company employs outsourcing service, industrial relationship disputes